Acyclic nucleoside phosphonates with 2-aminothiazole base as inhibitors of bacterial and mammalian adenylate cyclases - Břehová, Petra; Chaloupecká, Ema; Česnek, Michal; Skácel, Jan; Dračínský, Martin; Tloušťová, Eva; Mertlíková-Kaiserová, Helena; Soto-Velasquez, Monica P; Watts, Val J; Janeba, Zlatko (European journal of medicinal chemistry, 2021)
A series of novel acyclic nucleoside phosphonates (ANPs) was synthesized as potential adenylate cyclase inhibitors, where the adenine nucleobase of adefovir (PMEA) was replaced with a 5-substituted 2-aminothiazole moiety. The design was based on the structure of MB05032, a potent and selective inhibitor of fructose 1,6-bisphosphatase and a good mimic of adenosine monophosphate (AMP). From the series of eighteen novel ANPs, which were prepared as phosphoroamidate prodrugs, fourteen compounds were potent (single digit micromolar or submicromolar) inhibitors of Bordetella pertussis adenylate cyclase toxin (ACT), mostly without observed cytotoxicity in J774A.1 macrophage cells. Selected phosphono diphosphates (nucleoside triphosphate analogues) were potent inhibitors of ACT (IC50 as low as 37 nM) and B. anthracis edema factor (IC50 as low as 235 nM) in enzymatic assays. Furthermore, several ANPs were found to be selective mammalian AC1 inhibitors in HEK293 cell-based assays (although with some associated cytotoxicity) and one compound exhibited selective inhibition of mammalian AC2 (only 12% of remaining adenylate cyclase activity) but no observed cytotoxicity. The mammalian AC1 inhibitors may represent potential leads in development of agents for treatment of human inflammatory and neuropathic pain.
Keywords: Animals; vztah mezi dávkou a účinkem léčiva; neuralgie; buněčné linie; mikrobiální testy citlivosti; Prodrugs; Thiazoles; thiazoly; Acyclic nucleoside phosphonates; Molecular Structure; Adenylate Cyclase Toxin; Bordetella pertussis; Structure-Activity Relationship; lidé; Mice; Anti-Bacterial Agents; Adefovir; myši; Adenylate cyclase; Cell Line; molekulární struktura; Microbial Sensitivity Tests; organofosfonáty; Dose-Response Relationship, Drug; inhibitory adenylylcyklasy; Inhibitors; Bacillus anthracis; vztahy mezi strukturou a aktivitou; Adenylyl Cyclase Inhibitors; Neuralgia; zvířata; antibakteriální látky; Organophosphonates; adenylátcyklasový toxin; Humans